A bitter adjustment for German family capitalism: Succession and a changing ownership transfer regime - Isabell Stamm; Allan Sandham (Max Planck Institute for the Study of Societies, 2023)
Germany is known for its family-owned businesses that transfer ownership across generations. However, business owners in Germany increasingly envision selling their business beyond the family, which fundamentally changes the institutionalized way private ownership of businesses is transferred. In this paper, we analyze and explain this fundamental change in German family capitalism since the 1990s. Drawing on a sociology of ownership, we view family succession as a transfer regime and show how this regime has been problematized and gradually reframed. Based on analysis of a rich corpus of documents, archival materials, and twenty-seven expert interviews, we show how a new transfer regime - the exit regime - emerges, which coordinates ownership transfer among founders through matchmaking. Our study contributes to research on family capitalism and succession by demonstrating how family capital moves toward the financial sector without becoming financial capital as it loses the family and gains the founder as personalized points of reference. – – Deutschland ist für seine Familienunternehmen bekannt, die das Eigentum am Unternehmen innerhalb der Familie halten und es familienintern an die nächste Generation übergeben. Allerdings ziehen immer mehr Unternehmenseigentümer in Betracht, ihr Unternehmen an Externe zu verkaufen, wodurch sich die institutionalisierte Form des Eigentumstransfers von Unternehmen stark wandelt. In diesem Discussion Paper analysieren und erläutern wir diesen sich seit den 1990er-Jahren vollziehenden Wandel, der den Familienkapitalismus in Deutschland grundlegend verändert. Wir setzen uns aus der Perspektive einer Soziologie des Eigentums mit familieninterner Nachfolge als spezifischem Transferregime auseinander und zeigen, wie dieses Regime problematisiert und allmählich umgestaltet wurde. Anhand der Analyse einer umfangreichen Sammlung von Dokumenten und Archivmaterialien sowie von 27 Experteninterviews veranschaulichen wir, wie sich ein neues Transferregime - das Exit-Regime - herausbildet, das den Eigentumstransfer zwischen 'Gründern' über moderierte Vermittlung koordiniert. Unsere Studie leistet einen Betrag zur Forschung über Familienkapitalismus und Nachfolge, indem sie verdeutlicht, wie Familienkapital finanzialisiert wird, ohne dabei selbst zu Finanzkapital zu werden, solange die Familie mit dem Gründer als persönlichem Bezugspunkt ersetzt wird.
hdl:21.11116/0000-000D-F310-E
Keywords: 300; capitalism; family; ownership; regime change; succession; Eigentum; Familie; Kapitalismus; Nachfolge; Regimewandel